Validity of the BOT-2 Short Form for Korean School-Age Children: A Preliminary Study - Deukgeun Yoon; Dabin Choi; Misun Kim; Seokyeon Ji; Yoo-Sook Joung; Eun Young Kim (MDPI AG, 2024)
The Bruininks-Oseretsky Test of Motor Proficiency Second Edition (BOT-2) is the most common motor assessment in Korea. The BOT-2-Short Form (SF) is preferred over the complete form (CF) in settings with limited time. The present study aimed to assess the validity of the BOT-2 SF in Korean school-age children. First, we verified that the BOT-2 SF reflects developmental changes in motor skills. Second, we compared the BOT-2 SF scores to those of the BOT-2 CF. A total of 283 Korean school-age children performed the BOT-2. The differences in the BOT-2 SF point according to age group (7 years, 8-9 years, and 10-12 years) were analyzed. A correlation analysis of the standard scores between the BOT-2 SF and CF was conducted. The sensitivity and specificity of the BOT-2 SF were calculated in reference to its CF. Overall, the BOT-2 SF point scores increased with age. The correlation between the total scores of the BOT-2 SF and CF was strong. The BOT-2 SF had a sensitivity of 83% and specificity of 92%. This study has demonstrated the validity of the BOT-2 SF in Korean school-age children. The BOT2 SF can be useful in screening Korean school-age children with motor skills problems.